P-077 Using Registry Data to Identify Typical Use of Biological Pharmaceuticals in IBD Patients: A Case Study from Norway. (February 2017) - Lirhus, Sandre Svatun; Melberg, Hans Olav; Lie Høivik, Marte; Moum, Bjørn
Abstract : Background: During the last decade, several new and expensive drugs (including TNFα inhibitors and anti-integrins) have been introduced in IBD treatment. Little is known about the overall treatment pattern for these new biologic pharmaceuticals. What proportion of patients eventually receive biologics and how does this vary over time? How soon after being diagnosed with IBD do patients receive a biologic and which are most commonly used? How many switch to another biologic? The aim of this study was to describe treatment patterns for biologic pharmaceuticals by analysis of a nationwide patient registry that covers all patients with an IBD diagnosis in Norway. Methods: Data was collected from the Norwegian Patient Registry and includes information about every individual hospital treatment episode for IBD patients (ICD codes K50 and K51) from 2008 to 2015. Forty three thousand six hundred sixty-two IBD patients were identified in the registry. The data included information about gender, age, the date of the treatment (month and year) and use of biologics. Each event was associated with a unique patient identification number that made it possible to follow a patient across time. The date of diagnosis was set to the earliest observation in which the individual was observed with a K50 or K51 treatment episode, given that the patients had no IBD treatment episodes in the preceding years. Concurrently 2008 to 2009 were excluded since we had no information prior to 2008. In order to examine development over time, the patients were stratified based on the year of the first diagnosis. Results: During 2010 to 2014, there were 19, 887 new IBD patients out of which 6729 (33.8%) were diagnosed with Crohns' disease (CD) and 13, 158 (66.2%) with ulcerative colitis (UC). Among CD (UC) patients the proportion that received a biological pharmaceutical within one year after being diagnosed, increased from 12.2% (4.8%) in 2010% to 18.9% (7.7%) in 2014. For UC patients starting treatment in 2012 the median number of days from diagnosis to the first use of a biological pharmaceutical, was 335 days, while for CD patients it was 153 days. The most common pharmaceutical was infliximab and adalimumab (CD: 95.9%, UC: 88.8%). 27.8% of the patients who received a biological pharmaceutical switched biologics during the period. Among CD patients who were diagnosed between 2010 and 2014 and switched to another biologic, 22.8% did so within 100 days of the initiation of the first biologic. For UC patients the corresponding share was 25.5%. Conclusions: There was a consistent trend towards an increased use of biological pharmaceuticals over time, still, most have never been treated with biologics. For the patients who received biologics, a minority of about 20% switched to another biologic within 3 months, which may indicate that this subgroup of patients does not respond to their first biologic or they experience severe side-effects.